Quality improvement strategy of smoked catfish producer for e-commerce sales: a case study - Tian Nur Ma'rifat; Arief Rahmawan; Hefti Salis Yufidasari; Dwi Setijawati (AGROINTEK, 2026)
The expansion of digital technology, notably e-commerce, has revolutionized the business environment, offering immense potential for Indonesian SMEs. Small and medium-sized catfish processing businesses require improved process quality to reach online broader market. Meanwhile, there are several obstacles to improving quality in fish processing SMEs in Indonesia, include a lack of knowledge among producers and the absence of cold chain and food safety standards. Addressing these challenges is essential to enhance product quality, bolster SME competitiveness, and facilitate their integration into the digital marketplace. To solve this problem, this paper aims to identify consumer acceptance of the product, priorities of critical process, and priority procedures of smoked catfish production and e-commerce sales. This research employs a detailed single case study approach using both qualitative and quantitative methods. It starts with preliminary observations and in-depth interviews with business owners to understand the production process, quality challenges, and business goals, followed by consumer surveys and organoleptic tests to evaluate consumer acceptance of smoked catfish. The analysis method in this paper is modifications of House of Quality phases 1 and 2. The outcome of this research is the prioritization of measurable technical procedures as the focus for improvement by producers. By prioritizing critical processes such as smoking duration and implementing measurable operating procedures, SMEs can enhance product quality and meet e-commerce legal requirements, ensuring consistency and quality control throughout the production process.